Pharmacokinetic modeling and simulation for dose rationale of doripenem in neonates and infants. Issue 1 (February 2020) - Matsuo, Yumiko; Matsumoto, Sayaka; Wajima, Toshihiro; Matsubara, Kazuo
Abstract: The aims of this study were to construct a population pharmacokinetic model of doripenem in neonates and infants and to assess the dosing regimen for patients <3 months of age using Monte-Carlo pharmacokinetic/pharmacodynamic (PKPD) simulations. In the population pharmacokinetic analysis using 187 plasma concentrations from 47 neonates and infants, a two-compartment model well described plasma doripenem concentrations with the most significant covariates of chronological age and gestational age identified for the pharmacokinetics of doripenem. Monte-Carlo simulations suggested that the selected dosages for neonates and infants based on chronological age and gestational age (5 or 10 mg/kg) would provide ≥90% target attainment of 40%fT>MIC against MIC of 2 μg/mL in all age groups. These results would be useful for understanding the PKPD characteristics of doripenem, which could provide essential information on optimal therapeutic treatment for neonates and infants. Graphical abstract: Image 1